Self-Perception of Skills Specific to Professional Development in Physical Education and Sports - S. Drugau; L. Balint; R. Mijaica (Editura Universitatii Transilvania din Brasov, 2022)
The aim of our study was to identify the perception of the role of mentors and mentors in the initial vocational training process (mentoring process). Differences between the amounts of scores obtained in the questionnaire for self-assessment of the perception of specific competencies in physical education and sports (EFS) between the two samples of the preliminary study was 3.09 points, the group of mentors registered 115.17 points, and the group of mentors 118.26 points. The total cumulative value recorded by both samples is between 160-105 points according to the score of the questionnaire, which indicates that both samples have a very good perception of the level of development and manifestation of EFS specific competencies in carrying out initial teaching and training activities. The development and implementation of an effective mentoring process during the initial training period is impetuous and we believe that it will ensure the premises of a teaching career focused on continuous and effective professional development, and implicitly by expanding professional skills specific to physical education and sports.